The use of digital media in early childhood education: a reflection from skills and abilities - Cibele dos Santos Silva; Francisca Rodrigues Lopes (Revista Brasileira de Educação do Campo, 2023)
The use of media in early childhood education has found barriers, especially regarding teaching practice. This article aims to reflect on the challenges of teaching practice regarding the use of media in Early Childhood Education; also reflect on the concepts of competence and skill contextualizing with the documents that guide Early Childhood Education and some authors who discuss this subject. For this, qualitative research of bibliographic nature was carried out. Data analysis occurred through the interpretation of theoretical documents and texts, which pointed to the polyvalence of the concepts of competence and skills, which became popular with the implementation of the BNCC. The results of the research made it possible to show that the child should be protagonist in their interaction with the media world, thus, the school must ensure it’s social, cultural, digital and with its peers, overcoming traditionalism and the role centered on the teacher. They also showed that there is a paradox caused by the different positions of educators regarding the use of media in Early Childhood Education.